Intramedullary Spinal Cord Ependymoma after Posterior Fossa Ependymoma Resection: A Case Report - Pradhan, Benju R; Thapa, Bal K (Nepal Journal of Neuroscience, 2016)
We experienced a case in which multiple spinal cord dissemination was found 6 years after resection of the fourth ventricle ependymoma. A 17-year-old boy had undergone a subtotal resection of the fourth ventricle ependymoma and radiation therapy to the posterior fossa when he was 12 years old. Follow up CT head detected no residual tumor until he complained of back pain and pain in right thigh 6 years after surgery. MRI revealed multiple mass at D10-12 and L2-3. He underwent laminectomy and excision of tumor. This case reminds us to the necessity for long term radiological follow up including the spinal cord even in benign ependymoma, although it is still not clear for how long and how often we should do it.Nepal Journal of Neuroscience 13:48-50, 2016